Hacia el manejo de ecosistemas forestales - Aguirre Calderón, Oscar A. (Instituto de Ecología, A.C., 2016)
Traditional forest management is giving way to forest ecosystem management. This transition leads towards achievement and sustainability of the desired ecological and forest conditions, obtaining a sustained yield of products for the satisfaction of human needs.The development of forest ecosystem management models is a complex task, which involves the participation of several society sectors, as well as interdisciplinary professional teams for decision making. The objective is to achieve the greatest interaction between social requirements, ecological needs and ecological capabilities.In this article some principles of forest ecosystem management are presented, as well as the issues that running such a system implies, pointing out different aspects from traditional forest management. Several strategies for management forest landscape and forest stands, in order to contribute to a holistic forest resource management, are discussed.